On Mathematical Braids - Baldemor, Milagros (Data Science: Journal of Computing and Applied Informatics, 2019)
A braid is any sequence of crossings of the -strand braid with a positive number n, provided none of the strands are self-crossing. The idea is that braids can be organized into groups, in which the group operation is *, which means: “do the first braid on a set of strands, and then follow it with a second on the twisted strand”. This study dealt with the formulation of additional basic properties of mathematical braids and the connection of mathematical braids to exponential theorems. Moreover, the researchers developed a program that could generate the total number of crossings and the total number of generators in an n-strand braid with a positive number n.